Esmolol acutely alters oxygen supply‐demand balance in exercising muscles of healthy humans. Issue 8 (17th April 2018) - Proctor, David N.; Luck, J. Carter; Maman, Stephan R.; Leuenberger, Urs A.; Muller, Matthew D.
Abstract: Beta‐adrenoreceptor antagonists ( β blockers) reduce systemic O2 delivery and blood pressure (BP) during exercise, but the subsequent effects on O2 extraction within the active limb muscles are unknown. In this study, we examined the effects of the fast‐acting, β 1 selective blocker esmolol on systemic hemodynamics and leg muscle O2 saturation (near infrared spectroscopy, NIRS) during submaximal leg ergometry. Our main hypothesis was that esmolol would augment exercise‐induced reductions in leg muscle O2 saturation. Eight healthy adults (6 men, 2 women; 23–67 year) performed light and moderate intensity bouts of recumbent leg cycling before (PRE), during ( β 1 ‐blocked), and 45 min following (POST) intravenous infusion of esmolol. Oxygen uptake, heart rate (HR), BP, and O2 saturation (SmO2 ) of the vastus lateralis (VL) and medial gastrocnemius (MG) muscles were measured continuously. Esmolol attenuated the increases in HR and systolic BP during light (−12 ± 9 bpm and −26 ± 12 mmHg vs. PRE) and moderate intensity (−20 ± 10 bpm and −40 ± 18 mmHg vs. PRE) cycling (all P < 0.01). Exercise‐induced reductions in SmO2 occurred to a greater extent during the β 1 ‐blockade trial in both the VL ( P = 0.001 vs. PRE) and MG muscles ( P = 0.022 vs. PRE). HR, SBP and SmO2 were restored during POST (all P < 0.01 vs. β 1 ‐blocked). In conclusion, esmolol rapidly and reversibly increases O2 extraction within exercising muscles of healthy humans. Abstract : We used the β 1 blocker esmolol and near infrared spectroscopy to investigate the impact of acutely reducing systemic O2 delivery on real time oxygenation responses within exercising leg muscles. Esmolol attenuated the rise in heart rate and blood pressure, resulting in greater (compensatory) reductions in active muscle O2 saturation; these effects dissipated 45 min after discontinuing esmolol infusion. These findings highlight the dynamic link between systemic O2 delivery and active muscle O2 extraction.